Sickle cell anemia and early stroke detection and prevention in Nigeria - Ahmed, Kudirat Abdulkareem; Bello-Manga, Halima; Jordan, Lori C. (Frontiers in Stroke, 2024)
Sickle cell disease (SCD) is the most common hereditary blood disorder worldwide, and sickle cell anemia (SCA), the homozygous state of SCD, is the most common and severe variant of the disease. Nigeria has the highest burden of SCA in the world. Hemolysis and vaso-occlusion can lead to a wide range of complications, including stroke which is one of the most devastating manifestations of SCA with significant morbidity and mortality. SCA remains the leading cause of stroke in black children. Without any intervention, strokes occur in approximately 11% of children with SCA before their 20th birthday, with the greatest risk in very young children between 2 and 5 years of age. In resource-constrained countries, where the burden of SCA is highest, stroke is underreported, hence the need to develop strategies for stroke prevention and early detection. Improving awareness among healthcare providers and the community can significantly reduce stroke rates and improve stroke detection. The goal of this manuscript is to discuss the progress that has been made in stroke prevention and detection in children with SCA in Nigeria and outline current challenges and future goals. We believe that our experience will be valuable not only in Nigeria which has the highest burden of SCA globally, but also in other low- and middle-income countries.